-2+-4=

Simple and best practice solution for -2+-4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+-4= equation:


-2+-4=0

We simplify the equation to the form, which is simple to understand
-2+-4=0

We move all terms containing to the left and all other terms to the right.
0=0+2

We simplify left and right side of the equation.
0=+2

0=2

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

 

You can always share this solution

See similar equations:

| x^2-10=9x | | 6-7x=32-14x | | 3m+1=8 | | 2x^2-23x-12=0 | | 7x+14=4x+89 | | 8-2n=-4 | | 37-2x=16x+17 | | 3.0x^2-2.0=-2.0x | | 6x+11=-93-7x | | 20-4z=5z-25 | | 12p(3p-4)+3=5+4p(9p-2) | | 41n+18=49+42 | | 119-6x=2x+15 | | 12.5=n+1.5 | | 5a+8b+24c=27 | | -4(2p+3p)-5(4q+p)= | | 3(c-8)=c+4 | | 2.73x^2+1.47x-5.72=0 | | 141-7x=29x+21 | | y=0.75x | | x^4-2x^2-63=0 | | 50x^2-8=0 | | 10x+6=7x+18 | | 9x+1=9x+1 | | 5x^2-30x+25=0 | | 4x-9x-16=-5x+9-16 | | (5+p)-(p-q)-(3p+4q-6)= | | 5x-7=5(x+7) | | X^2-5X+40=0 | | 10(n+3)=2(15+5n) | | 10x-9+9x-5=9x-3 | | 2x-128=0 | | 2h^2+13h-7=0 | | (6x-3)+(3x+2)= | | 99-2x=5x+22 | | 5(x+9)+5(-6x-1)=-26(x-1) | | 4x-3=5+12x | | 5x+25= | | 1.2x-6=0 | | 12x-7-x-10=15x+8+x-3 | | 245(82X-56)=517X+2134 | | 16y^2=81 | | n^2+7n+14=5 | | x^2-3=-2 | | 25h^2-16=0 | | 3x^2+8x-9=2x | | 6x+15=4x+29 | | 64k^2-49=0 | | x^2+9x+160=0 | | 81-4b^2= | | 3w+7=x | | 8a-10=9+10a | | 6c^2+25c-9=0 | | b^2-6b-40=0 | | 25q^2-16=0 | | (7b+3)(4b-12)=0 | | 5(x-2)+52=-2x | | 5x+2=4x+7 | | 11x^2-x=3 | | 6x+15=4x+11 | | Y=(0.6)2 | | (x+8)+(x+3)=21 | | Y=(0.6)1 | | Y=(0.6)0 | | 4(y-15)=4y |

Equations solver categories